(untitled) (Research, Society and Development, 2022)
The pandemic of the new coronavirus intensified several educational problems and Emergency Online learning emerged as an alternative to some of those nowadays impasses. However, this strategy contributed to the construction of several teaching barriers, among them, we highlight the lack of promotion of methods focused on the principles of an Inclusive Education for everyone. This article in bringing measures of accessory through the use of a software that facilitates the visualization of the Sign Language Interpreting Professional (SLIP), which is a resource that avoids excessive visual information and allows the simultaneous display of SLIP with the presented lesson material. The methodological process had a qualitative approach that went through a deaf student validation, presenting satisfactory results and indicating the importance of expanding inclusion in teaching labour, as well as the need for incentives to advance studies in this relevant area that is often forgotten.